Civic and citizenship education, global citizenship education, and education for sustainable development: an analysis of their integrated conceptualization and measurement in the international civic and citizenship education study (ICCS) 2016 and 2022 - Valeria Damiani; Julian Fraillon (Large-scale Assessments in Education)
Abstract Globalization and its impact on contemporary societies have gained new impetus with the notions of global citizenship education (GCED) and education for sustainable development (ESD), considered, together with civic and citizenship education (CCE), as a means for promoting students’ engagement in global/local issues and providing them with the awareness and skills to develop a deeper understanding of, and response to, contemporary issues. Research has shown that GCED and ESD, intended as two interrelated and intersecting fields, have strong associations with CCE and how citizenship is conceived in the post-national and global era. This paper aims to examine the issue of GCED/ESD achievement measurement within the field of civic and citizenship education. Combining analysis of the assessment frameworks and of data from the IEA ICCS (2016, 2022) achievement test (the civic knowledge test), it discusses the integration of the conceptualization and measurement of student achievement in civic knowledge with an ex-post operationalization and measurement of student achievement in concepts and content associated with GCED and ESD (for ICCS 2016) and subsequently analyses the associations between test items related to the GCED/ESD domain and those related to “the other CCE” domain in ICCS 2022. Results highlighted the progressive relevance of GCED/ESD in the ICCS studies and the blurred boundaries between GCED/ESD and CCE both in ICCS 2016 and 2022. In disentangling the implicit, growing interrelationship among these areas (theoretically and from a measurement perspective), research findings also showed the evolution of the concept of civic and citizenship education itself.